Detection of potential drug-drug interactions in prescriptions dispensed in hospital pharmacy - LIYA SIBY,; ATHIRRA SUKUMARAN,; ESWARAN MAHESWARI, (International Journal of Pharma and Bio Sciences, 2016)
This prospective observational study examined the severity, type and frequency of potential drug-drug interactions (PDDIs) in prescriptions dispensed in the hospital pharmacies of M.S. Ramaiah Memorial Hospital and M.S. Ramaiah Hospital, Bangalore, Karnataka. A total of 500 prescriptions were collected over a period of 5 months. PDDIs were identified and analysed using Micromedex database. The frequency of PDDIs was 71.8%, with at least one interacting combination with major (14.20%), moderate (72.70%) and minor (13.09%) interactions. Out of the total PDDIs identified, 60% were pharmacodynamic interactions, 38% were pharmacokinetic interactions and 2% had interaction of unknown mechanism. The largest number of active drugs prescribed with major PDDIs were related to the cardiovascular system (32.63%), central nervous system (22.28%), gastrointestinal tract and drug metabolism (13.37%).The results of the present study showed a high frequency of PDDIs in prescriptions received at hospital pharmacies.